دور مدقق الحسابات الخارجي في قياس العلاقة بين أساليب ودوافع المحاسبة الإبداعية في الشركات المساهمة السّورية /دراسة ميدانيّة/ - الأمين, ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى دراسة دور المدقق الخارجي في قياس العلاقة بين أساليب المحاسبة الإبداعيّة المطبّقة في الشّركات المساهمة السّوريّة ودوافعها، من خلال دراسة ميدانيّة أجريت على مدققي حسابات الشّركات المساهمة. ولتحقيق هدف البحث تمّ تصميم استبانة كأداة لجمع البيانات من أفراد مجتمع البحث المكوّن من مدققي الحسابات المعتمدين من قبل وزارة المالية، والمسموح لهم بتدقيق حسابات الشركات المساهمة تم توزيعها على (300) مدقق حسابات من أصل (493) مدقق حسابات، استُردّ منها (125) استبانة، وتمّ تفريغ (115) استبانة كونها صالحة للتحليل. أثبت البحث وجود تفاوت في تقدير المدقق الخارجي لدرجة تطبيق الشركات المساهمة السّوريّة لأساليب المحاسبة الإبداعية عند إعدادها لقوائمها المالية يعزى للمؤهّل العلمي، والشهادة المهنية المحاسبية, والتخصص المحاسبيٍ الدقيق. وظهرت أقوى علاقة بين أسلوب التّأثير في بنود قائمة المركز المالي ودافع تحقيق أرقام محدّدة للرّبح، ونالت العلاقة بين تجنّب التّكاليف السّياسيّة وأسلوب التّأثير في قائمة الدّخل المرتبة الثّانية من حيث مستوى القوّة. وأظهرت نتائج الارتباط بين أساليب الإدارة ودوافعها أنّه لتحقيق دافع معيّن قد تتبع الإدارة أكثر من أسلوب، إذ أنّها قد تطبّق مثلاً أسلوب التّأثير في بنود قائمة المركز المالي، وقائمة التّدفقات النّقدية، والتّمويل خارج الميزانيّة، في سبيل تحقيق أرقام محدّدة للرّبح.The study aims to determine the level of the relationship between creative accounting techniques applied in shareholding corporations and their motivation through a field study that was undertaken on the auditors of shareholding companies. To achieve the objective of this study, a questionnaire was designed as a tool to collect data from the population of the study which is composed of auditors appointed by the Ministry of Finance, and authorized to audit shareholding companies. The questionnaire was distributed to 300 out of 493 auditors. 125 questionnaires were returned, and 115 questionnaires were suitable for analysis..The study showed difference in estimation of external auditor of the degree of application of Syrian companies for creative accounting techniques in preparing financial statements due to scientific qualification, the certificate of professional accounting, and accounting specialization. And a stronger relationship appeared between the influence technique on the items of the financial position statement and the motivation to achieve specific figures of profit, and the relationship between political costs avoidance and the technique of influence on income statement got the second highest on the level of power. Correlation results between management techniques and their motivation showed that to achieve a certain motive, management might follow more than one technique, they may apply, for example, a technique that influence the items of statement of financial position, statement of cash flows, off-balance sheet financing, in order to achieve specific figures of profit.